Effect of Transcutaneous Upper Eyelid Blepharoplasty on Blink Parameters and Lipid Layer Thickness - Siyi Zhang (Frontiers Media S.A., 2021)
Purpose: This study aimed to investigate the effect of transcutaneous upper eyelid blepharoplasty on lipid layer thickness (LLT) and blink parameters in young women during the early postoperative period.Methods: This prospective study included 110 eyes of 55 young female patients (age range, 19–31 years) who underwent transcutaneous upper eyelid blepharoplasty. The LLT and blink parameters measured using a LipiView interferometer were recorded before the surgery and 1 week and 1 month after the surgery. Ocular Surface Disease Index (OSDI) score, noninvasive tear film breakup time (NITBUT), and palpebral fissure height (PFH) measurements were also performed at each time point.Results: The number of blinks significantly decreased (P < 0.001), and the number of partial blinks and partial blink rate (PBR) significantly increased 1 week after the surgery (P = 0.002 and P < 0.001); they all returned to baseline in 1 month. The LLT and OSDI score increased significantly 1 week and 1 month after the surgery (P < 0.001 and P < 0.001). A significant increase in the NITBUT and a significant decrease in the PFH were observed 1 week after the surgery (P < 0.001 and P < 0.001), and the values returned to baseline 1 month after the surgery. No clinical correlation was found between blink parameters and ocular surface parameters.Conclusions: Transcutaneous upper eyelid blepharoplasty led to a change in blink parameters and ocular surface parameters during the early postoperative period. However, this influence was temporary, and the transitory change in blink parameters had no effects on the ocular surface environment.